Avaliação da lei de cotas como instrumento de inserção de jovens com deficiência no mercado de trabalho no Ceará - Araújo, Thaynah Barros de (2018)
This study evaluated the Quota Law as an instrument for insertion of people with disabilities in the formal labor market in the State of Ceará, considering the actions developed by the Center for Inclusive Professionalisation for the Person with Disabilities (Cepid). The general objective was to evaluate the Quotas Law as an instrument for insertion of young people with disabilities into the formal labor market in Ceará, identifying their challenges and perspectives, based on the actions carried out by Cepid. The specific objectives were to identify the socioeconomic profile of young people with disabilities, assisted by Cepid; to verify the types of disability that Cepid has been inserting in the world of work; understand how access to formal work materializes in the perception of young people with disabilities accompanied by Cepid; to learn how the managers and professionals of Cepid perceive compliance with the Law of quotas in Ceará, based on the actions carried out by this equipment. Our research proposal has also proposed to promote an evaluation that goes beyond the measurement of efficiency, effectiveness and effectiveness of public policy. Despite the diversity of evaluative paradigms, the hegemonic remains the positivist. In order to break with this trend, we draw inspiration from the perspective of in-depth evaluation through which we intend to stimulate new studies, research and debates against hegemonic ones with regard to the problematic on-screen. As for the methodological aspects, we carried out bibliographic research in books and periodicals on the proposed theme, the diary and the trip to the field were essential for its materiality. The present research has a qualitative and quantitative nature, since we understand that an in-depth evaluation goes beyond the numerical / measurable aspects of public policy and covers its meanings / meanings. We used semi-structured interviews, through which the evaluation of the data collected was through content analysis. In the development of the research, we problematize the access of young people with disabilities to the labor market, validating themselves of the legal supports. We discussed the obstacles to the materialization of the Quota Law, in order to propose mechanisms to qualitatively effect the right of these subjects to work. As results, we critically discuss the actions of the Government of Ceará, through Cepid, regarding the labor inclusion of the public on screen, so that we identify that despite the expansion of the number of PcD in the labor market, this access has promoted an inclusion that paradoxically excludes this segment.